PENGARUH BRAND PERSONALITY DAN PERCEIVED VALUE TERHADAP CUSTOMER SATISFACTION YANG DIMEDIASI OLEH TRUST PADA MATAHARI DEPARTMENT STORE KOTA BANDA ACEH - Syarifah Salqaura; Farid Farid (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
This study aims to measure the influence of Brand Personality and Perceived Value on Consumer Satisfaction which is mediated by Trust in Matahari Department Store Customers in Banda Aceh City. The sample used in this study was Matahari Department Store Customers in Banda Aceh City, amounting to 200 respondents. The sampling technique used was purposive sampling. Structural Equation Modeling (SEM) is used as an analytical method to determine the effect of the variables involved. Based on the results of analysis from SEM identified that Brand Personality and Perceived Value have an effect on Consumer Satisfaction, Brand Personality and Perceived Value have an effect on Trust, Trust has an effect on Consumer Satisfaction, Trust mediates Brand Personality and Perceived Value on Consumer Satisfaction.